An approach to mobility management in Cellular IP networks utilising power-save mode of IEEE 802.11. (21st May 2008) - Lee, Joungwoong; Kimura, Shigetomo; Ebihara, Yoshihiko
Although FMIPv6, HMIPv6, and F-HMIPv6 have been proposed as enhancements to Mobile IPv6, they still have some technical barriers for fast and seamless handovers. We propose an intelligent mobility protocol benefiting from Cellular IP. To speed up the entire handover procedure, our proposed scheme enables L2 and L3 handovers to be performed in parallel by utilising power-save mode of IEEE 802.11. We provide analytical considerations on the handover latency and packet delivery cost of each protocol. Through our simulation experimental results, we have verified that our proposed scheme shows much better performance over the others under various parameter sets.